2007
DOI: 10.1002/ajmg.a.31990
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of congenital cataracts, sensorineural deafness, Down syndrome‐like facial appearance, short stature, and mental retardation: Two additional cases

Abstract: An apparently new syndrome of congenital cataracts, sensorineural deafness, Down syndrome-like facial appearance, short stature, and mental retardation was described by Gripp et al. 1996. The authors reported on two unrelated patients with congenital cataracts, sensorineural deafness, distinctive facial appearance, mental retardation, postnatal short stature, and skeletal changes. We report on two additional patients with findings most similar to the reported patients by Gripp et al. 1996, including bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…To the best of our knowledge, the terminal 11q monosomy, spanning 1.97-2.11 Mb, in patient 3, is one of the smallest ever described in the literature [Keppler-Noreuil et al, 2007]. Her phenotype was in accordance with the suggestion by KepplerNoreuil et al [2007] that a terminal 2 Mb 11qter monosomy could not be associated with typical Jacobsen anomalies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…To the best of our knowledge, the terminal 11q monosomy, spanning 1.97-2.11 Mb, in patient 3, is one of the smallest ever described in the literature [Keppler-Noreuil et al, 2007]. Her phenotype was in accordance with the suggestion by KepplerNoreuil et al [2007] that a terminal 2 Mb 11qter monosomy could not be associated with typical Jacobsen anomalies.…”
Section: Discussionsupporting
confidence: 86%
“…Moynihan et al identified another putative deafness locus, DFNB20 in 11q25, which was homozygous in a consanguineous family with histiocytosis, joint contractures and deafness [Moynihan et al, 1998;Moynihan et al, 1999]. Some patients with deafness and 11q monosomy, excluding TECTA but including DFNB20, were reported in the literature [Giampietro et al, 2006;Keppler-Noreuil et al, 2007]. Our observation of three patients with DFNB20 deletion, but conservation of TECTA, tends to confirm the hypothetic role of DFNB20 in Jacobsen hearing impairment.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…3 Additional cases with a superimposing phenotype had subsequently been reported. 4,5 More recently, MAF (v-maf, avianmusculoaponeurotic-fibrosarcoma-oncogene-homolog, MIM#177075) was identified as the gene implicated in this disorder, 6 and the eponym Aymé-Gripp syndrome (AYGRPS, MIM#601088) was hence proposed for this condition, which is invariantly characterized by growth defect, CNS abnormalities, intellectual disability (ID), epilepsy, congenital cataract, bilateral SNHL, and a distinctive facial gestalt. 6 Clinical variability has been reported in some instances.…”
Section: Introductionmentioning
confidence: 99%